Estilos de aprendizaje: distintas maneras de aprender las Ciencias Naturales en el tercer grado de Educación General Básica - Chamba Maza, Rosario Yadira (2025)
This research deals with "Learning Styles: Different Ways of Learning Natural Sciences". It has the general objective: To determine the influence of learning styles on strengthening the learning of Natural Sciences in the third grade of Basic General Education at the "Miguel Riofrío" Educational Unit. To fulfill this objective, three specific objectives were developed. The first was: To diagnose the learning of Natural Sciences in the third grade of Basic General Education at the "Miguel Riofrío" Educational Unit. The second: To plan a pedagogical proposal using learning styles to strengthen the learning of Natural Sciences. The third: To evaluate the influence of learning styles on strengthening the learning of Natural Sciences. To carry out this study, a descriptive type of research with a mixed approach was used. The design was quasi-experimental. In the development of the research, the scientific, statistical, analytical, synthetic, and descriptive methods were used. Among the techniques are: diagnostic evaluation, interview, pre- and post- evaluation. Similarly, the instruments used were the pre- and post-evaluation for data collection. The population taken into account for the research was from the "Miguel Riofrío" Educational Unit, and through a simple non-probabilistic sampling, seventeen students and one teacher were selected. Similarly, when applying the improvement proposal, it was possible to determine that working with activities with different learning styles significantly improves the academic performance of the students, allowing them to be the protagonists of it. Therefore, this methodology provides many benefits for learning Natural Sciences, being essential and primary tools in the academic development of the student. Hence, it is essential to use innovative methodologies such as learning styles, as they allow students to be the axis of the process.